The IDO–AhR Axis Controls Th17/Treg Immunity in a Pulmonary Model of Fungal Infection - de Araújo, Eliseu Frank; Feriotti, Claudia; Galdino, Nayane Alves de Lima; Preite, Nycolas Willian; Calich, Vera Lúcia Garcia; Loures, Flávio Vieira (Frontiers in Immunology, 2017)
In infectious diseases, the enzyme indolemine 2,3 dioxygenase (IDO) that catalyzes the tryptophan (Trp) degradation along the kynurenines (Kyn) pathway has two main functions, the control of pathogen growth by reducing available Trp and immune regulation mediated by the Kyn-mediated expansion of regulatory T cells via Aryl hydrocarbon receptor (AhR). In pulmonary paracoccidioidomycosis caused by the dimorphic fungus Paracoccidioides brasiliensis, IDO was shown to control the disease severity of both resistant and susceptible mice to the infection, however, only in resistant mice IDO is induced by TGF- signaling that confers a stable tolerogenic phenotype to DCs. Additionally, in pulmonary PCM the tolerogenic function of plasmacytoid dendritic cells (pDCs) was linked to the IDO activity. To further evaluate the function of IDO in pulmonary PCM, IDO deficient (IDO-/-) C57BL/6 mice were intratracheally infected with P. brasiliensis yeasts and the infection analyzed at three post-infection periods regarding several parameters of disease severity and immune response. The fungal loads and tissue pathology of IDO-/- mice were higher than their wild type (WT) controls resulting in increased mortality rates. DCs from infected IDO-/- mice expressed elevated levels of costimulatory molecules and cytokine IL-6 associated with reduced production of IL-12, TNF-, IL-1 TGF- and IL-10. This response was concomitant with a marked reduction in AhR production. The absence of IDO expression caused an increased influx of activated Th17 cells to the lungs with a simultaneous reduction in Th1 and Treg cells. Accordingly, the suppressive cytokines IL-10, TGF-, IL-27 and IL-35 appeared in reduced levels in the lungs of IDO-/- mice. Interestingly, in the lungs of IDO-/- mice an upregulated differentiation of innate lymphoid cells from the ILC3 phenotype was accompanied by a decreased expansion of ILC1 and NK cells. In conclusion, the immunological balance mediated by the axis IDO/AhR is fundamental to determine the balance between Th17/Treg cells and control the severity of pulmonary PCM.